Implicações éticas do método fenomenológico: o acesso ao estrangeiro na Quinta Meditação cartesiana - Weidmann, Artur Ricardo de Aguiar (2010)
This study aims at examining the possibility of an ethical interpretation of the Fifth Cartesian Meditation from a phenomenology of the own and the alien. The methodology used articulates some historic topics in a systematic reconstruction of fundamental concepts of the Husserlian text based on the Cartesian Meditations and also with the help of specialized bibliography. The following steps were taken to achieve that aim. First, the examination and explicitation of the theoretical solipsism problem, the notion of transcedental Ego in Husserl´s work and the constitution of the transcendental Intersubjectivity. The importance that such notion has will be taken into account referring to our conceptual construction on the possibility of consciences communication, that is, of the transcendental Intersubjectivity constitution and, consequently, the constitution of the objective world. The second step will start from the results of the investigation about the constitution of intersubjectivity to examine the category of alterity under the possibility of elaborating a phenomenological ethics based on the concept of responsibility described from inter-human relationships. Contemporary phenomenologists works, like Ricoeur, Lévinas e Waldenfels, will be used as mediators so that we can investigate whether the description of the experience with the alien (not-own) can be read in Husserl as an ethical problem. From those results we will investigate the possible ethical implications contained in the intersubjectivity category. The hypothesis we will be working with is that Husserl would have left open, from the Fifth Meditation, the possibility to think the beginning of a conscience of responsibility from the relation of an own sphere and a alien sphere, as thought of by some of his disciples, which would allow us to think of ethics from Husserl and not the contrary.